Two new acoels (Acoelomorpha) of the genus Haplogonaria from the northwest Atlantic - Hooge, Matthew D.; Tyler, Seth (Zootaxa, 2015)
Two previously unknown species of Haplogonaria (Acoela), H. schillingi sp. nov. and H. baki sp. nov., are described from the coastline of Maine, USA. The two species are morphologically similar to each other but H. schillingi can be distinguished from H. baki by its red pigmentation, its possession of a large genital atrium that branches posteriorly to the seminal vesicle and anteriorly to the vagina, a seminal vesicle that is more ellipsoid-shaped than spherical, and a well-defined wall in the seminal bursa.        We provide a description of the new species using live observation, light microscopy of serial sagittal sections, and confocal microscopy imaging of F-actin. We compare the morphology of the new species with other members of the genus and discuss the phylogenetic position of H. schillingi in light of conflicting morphological and molecular data.